Aberrant hyperactivation of cytotoxic T-cell as a potential determinant of COVID-19 severity. (August 2020) - Kang, Chang Kyung; Han, Gi-Chan; Kim, Minji; Kim, Gwanghun; Shin, Hyun Mu; Song, Kyoung-Ho; Choe, Pyoeng Gyun; Park, Wan Beom; Kim, Eu Suk; Kim, Hong Bin; Kim, Nam-Joong; Kim, Hang-Rae; et al.
Highlights: COVID-19 can deteriorate at the 2nd week of illness despite decreasing viral loads. We analyzed PBMCs of severe or mild COVID-19 cases at the 1st and 3rd week of illness. Cellular responses were not different between two groups at the 1st week of illness. Higher T-cell proliferation, activation, and cytotoxicity was noted in severe cases at the 3rd week. Aberrant hyperactivation of cytotoxic T-cell may contribute to severe COVID-19 pneumonia. Abstract: Objectives: We hypothesized that immune response may contribute to progression of coronavirus disease-19 (COVID-19) at the second week of illness. Therefore, we compared cell-mediated immune (CMI) responses between severe and mild COVID-19 cases. Methods: We examined peripheral blood mononuclear cells of laboratory-confirmed COVID-19 patients from their first and third weeks of illness. Severe pneumonia was defined as an oxygen saturation ≤93% at room air. Expressions of molecules related to T-cell activation and functions were analyzed by flow cytometry. Results: The population dynamics of T cells at the first week were not different between the two groups. However, total numbers of CD4 + and CD8 + T cells tended to be lower in the severe group at the third week of illness. Expressions of Ki-67, PD-1, perforin, and granzyme B in CD4 + or CD8 + T cells were significantly higher in the severe group than in the mild group at the third week. In contrast to the mild group, the levels of their expression did not decrease in the severe group. Conclusions: Severe COVID-19 had a higher degree of proliferation, activation, and cytotoxicity of T-cells at the late phase of illness without cytotoxic T-cell contraction, which might contribute to the development of severe COVID-19.